OEDIPE, a software for personalized Monte Carlo dosimetry and treatment planning optimization in nuclear medicine: absorbed dose and biologically effective dose considerations. Issue 4 (13th November 2014) - Petitguillaume, A.; Bernardini, M.; Broggio, D.; de Labriolle Vaylet, C.; Franck, D.; Desbrée, A.
Abstract : For targeted radionuclide therapies, treatment planning usually consists of the administration of standard activities without accounting for the patient-specific activity distribution, pharmacokinetics and dosimetry to organs at risk. The OEDIPE software is a user-friendly interface which has an automation level suitable for performing personalized Monte Carlo 3D dosimetry for diagnostic and therapeutic radionuclide administrations. Mean absorbed doses to regions of interest (ROIs), isodose curves superimposed on a personalized anatomical model of the patient and dose-volume histograms can be extracted from the absorbed dose 3D distribution. Moreover, to account for the differences in radiosensitivity between tumoral and healthy tissues, additional functionalities have been implemented to calculate the 3D distribution of the biologically effective dose (BED), mean BEDs to ROIs, isoBED curves and BED-volume histograms along with the Equivalent Uniform Biologically Effective Dose (EUD) to ROIs. Finally, optimization tools are available for treatment planning optimization using either the absorbed dose or BED distributions. These tools enable one to calculate the maximal injectable activity which meets tolerance criteria to organs at risk for a chosen fractionation protocol. This paper describes the functionalities available in the latest version of the OEDIPE software to perform personalized Monte Carlo dosimetry and treatment planning optimization in targeted radionuclide therapies.